Comparative analysis of sports workers and kinesiologists: a paradox of similar jobs but distinct professional profiles - Giovanni Esposito; Rosario Ceruso; Giuseppe Giardullo; Sara Aliberti; Gaetano Raiola (Human Movement)
Purpose Recently, in Italy, two professions have been defined in the field of sports and physical activities: the sports worker, trained by sports organisations, and the kinesiologist, who holds a degree in exercise and sports sciences. This distinction is essential to ensure quality standards and appropriate regulations, avoiding duplication and confusion among professionals and clients. This study aimed to understand stakeholders’ knowledge regarding the different professional roles involved in preventive and adapted physical activities, basic and advanced physical exercise, and functional re-athletisation.